The Effect of E-Learning Training and Work Motivation on Employee Performance of PT Japfa Comfeed Indonesia Tbk Sidoarjo Unit - Diaz Syifa Rahmania; Siti Ning Farida (Universitas KH. Abdul Chalim Mojokerto, 2025)
The study aims to show the effect of e-learning training and work motivation on the performance of employees of PT Japfa Comfeed Indonesia Tbk Sidoarjo Unit. The type of research used is quantitative with an associative approach and uses primary and secondary data. This study used non-probability sampling, namely ourposive sampling of 93 respondents. The data analysis technique used multiple linear regression analysis, but before that, validity, realism and classical assumptions were tested with the SPSS 27 software tool. The results of the study show that e-learning training has a significant positive effect on employee performance. Work motivation affects employee performance. E-learning training and work motivation have a simultaneous effect on employee performance. E-learning training and work motivation have a simultaneous effect on employee performance. This research can complement existing theories and can be a reference for PT Japfa Comfeed Indonesia Tbk Sidoarjo Unit in improving employee performance, especially in terms of training or human resource development.